What we did on our holiday [videorecording (DVD)] - Hamilton, Andy, 1954-; Pike, Rosamund, 1979-; Tennant, David, 1971-; Connolly, Billy (Lionsgate, 2014)
Doug and Abi take their kids on a family vacation. Surrounded by relatives, the kids innocently reveal the ins and outs of their family life and many intimate details about their parents. It's soon clear that when it comes to keeping a big secret under wraps from the rest of the family, their children are their biggest liability.